2020
DOI: 10.1111/liv.14703
|View full text |Cite
|
Sign up to set email alerts
|

Terlipressin has stood the test of time: Clinical overview in 2020 and future perspectives

Abstract: Vasoactive drugs form the mainstay of therapy for two of the most important complications of liver disease: hepatorenal syndrome (HRS) and acute variceal bleed (AVB). With cumulative evidence supporting the use in cirrhosis, terlipressin has been recommended for the management of HRS and AVB. However, owing to the safety concerns, terlipressin was not approved by food and drug administration (FDA) until now. In this review, we discuss the pharmacology and the major practice‐changing studies on the safety and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 108 publications
(204 reference statements)
0
66
0
2
Order By: Relevance
“…Cardiovascular adverse effects are common with terlipressin and need to be monitored strictly. 47 A multicenter, randomized, placebo-controlled double-blind study to confirm efficacy and safety of terlipressin in subjects with hepatorenal syndrome type 1 (the CONFIRM study) trial was completed on July 24, 2019, for 300 cases at 64 North American transplant centers (https://clinicaltrials.gov/ct2/show/study/NCT02770716). The study has not been published, but it would affect the management of those with hepatorenal syndrome type 1 and liver transplantation patients in general.…”
Section: Terlipressinmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular adverse effects are common with terlipressin and need to be monitored strictly. 47 A multicenter, randomized, placebo-controlled double-blind study to confirm efficacy and safety of terlipressin in subjects with hepatorenal syndrome type 1 (the CONFIRM study) trial was completed on July 24, 2019, for 300 cases at 64 North American transplant centers (https://clinicaltrials.gov/ct2/show/study/NCT02770716). The study has not been published, but it would affect the management of those with hepatorenal syndrome type 1 and liver transplantation patients in general.…”
Section: Terlipressinmentioning
confidence: 99%
“…These surgical innovations would certainly affect the future practice of perioperative physicians. • Terlipressin: Kulkarni et al 47 This systematic review found that documented mortality benefits with terlipressin therapy in hepatorenal syndrome and acute variceal bleeding. Cardiovascular adverse effects are common with terlipressin and need to be monitored strictly.…”
Section: Machine Perfusionmentioning
confidence: 99%
“…Tidak terdapat penelitian yang melaporkan data tentang lama rawat inap di rumah sakit. 18,19 Tamponade balon (balloon tamponade) sangat efektif dalam mengontrol perdarahan akut pada 90% pasien meskipun sekitar 50% terjadi perdarahan ulang saat balon dikempiskan. Namun, hal ini terkait dengan komplikasi serius seperti ulserasi esofagus dan pneumonia aspirasi pada hingga 20% pasien.…”
Section: Terlipressin Pada Perdarahan Varises Esofagusunclassified
“…Namun pada penelitian ini, tidak didapatkan manfaat kelangsungan hidup hingga hari ke-180 (p>0,05). 18 Terlipressin juga telah terbukti lebih unggul dibandingkan terapi alternatif untuk SHR yang biasa digunakan di Amerika Utara. Cavallin et al 23 melakukan random control trial (RCT) prospektif yang membandingkan terapi terlipressin dengan kombinasi midodrine dan ocreotide, dan kedua kelompok menerima infus albumin harian.…”
Section: Terlipressin Pada Sindrom Hepatorenalunclassified
“…4 Terlipressin (Tp) is the recommended standard of care for acute variceal bleed and HRS. [5][6][7] The role of Tp has also been evaluated in multiple other conditions, such as preventing paracentesis-induced circulatory dysfunction, refractory ascites, septic shock, and perioperatively during hepatobiliary surgery and liver transplantation but with limited success. 7 Tp reduces portal blood flow and portal pressure and increases systemic vascular resistance (SVR) and renal perfusion.…”
mentioning
confidence: 99%